Gendered patterns of adults' and children's time and access to technology and infrastructure in rural Uganda - Rosemary Emegu Isoto; Irene Nakamatte; Bernard Bashaasha; Sundus Saleemi (University of Bonn, Center for Development Research (ZEF), 2024)
This study analyses the time use patterns of men, women and children in rural areas of Uganda. The aims are to 1. Map the gendered patterns of time allocation to paid and unpaid work, total work and leisure. 2. Analyze the differences in individuals' time allocation in various household types and income levels 3. Assess the relationship between time use patterns, diets and productivity and 4. Assess agricultural and domestic technologies and access to infrastructure in their relationship to patterns of time use. The study was conducted in four regions of Uganda. A survey of rural households collected information on the time spent on different activities in the 24 hours by one adult woman, an adult man and the eldest child above age 10. Time Use Patterns: Men predominantly spend more time on paid work and leisure compared to women, reflecting traditional gender roles. Women are heavily involved in unpaid work, such as domestic and caregiving tasks, while men dedicate considerably less time to unpaid work. The gap in time allocation between men and women persists across different household sizes and compositions, highlighting the strong influence of sociocultural norms. Rural Ugandans; men, women and children in poor households generally spend more time on work than those in non-poor households. Hours of total work by both men and women increase as the level of formal education increases; among women with formal education, time on unpaid work reduces as their education level increases and time on paid work increases. Children often support in household tasks, particularly in large households, where they spend more time on unpaid work. Single adult households headed by men exhibit different time allocation patterns compared to dual adult households, where women and children share the burden of unpaid work. Children in dual-adult households spend more time on learning activities than those living in singleadult households. Time Use and Technologies: The majority of households in rural areas rely on handheld agricultural tools, with fewer households utilizing animal-pulled or mechanized technologies. Access to digital technologies was relatively common but basic phones were more prevalent than smartphones. Domestic technologies such as basic cooking stoves and pumps were also uncommon; washing machines and refrigerators/freezers were absent in rural households. Access to domestic and agricultural technologies, interacts with time allocation, with implications for women's paid work and leisure. Women in households with no access to agricultural technologies spend the most time on unpaid work. Mechanized technologies increase men's participation in paid work and reduce women's time spent on unpaid work, providing opportunities for reallocation of time. Time Use and Infrastructure: Access to infrastructure was limited, with only a minority of households having piped water, or electricity grid connections. Women spend more time on total work, particularly unpaid work, in households without access to piped water or electricity, underscoring the gendered impact of infrastructure availability. The distance to all-weather roads and water sources influences time allocation, with variations observed in commuting time and unpaid work among children and adults. Distance to the water source is associated with women's time use patterns; women in the lowest income quintile spend more time in paid work and less in unpaid work when the distance to the water source is less than the sample average. Boys in households closer to the water source spend less time in unpaid work than those nearer the water source, however, this reduction in their time in unpaid work appears to increase girls' time in unpaid work. Overall, children in households with a distance to an all-weather road less than the sample average spend less time commuting and have more leisure time. Children's Diets and Women's Time Use: Women living with children who consumed at least 5 food groups spend more time on both paid and unpaid work compared to those with children consuming fewer food groups. Specifically, women in households where children had at least 5 food groups spent 4.6 hours on paid work and 5.8 hours on unpaid work, while those with children consuming less than 5 food groups spent 4.1 hours and 4.8 hours, respectively. Additionally, women in households with children consuming at least 5 food groups spent significantly less time on leisure activities. Furthermore, within households where children had at least 5 food groups, children were less involved in total work, indicating a potential alleviation of household responsibilities for them. Men in these households were not involved in unpaid work.
Keywords: J22; J16; B54; 330; Time-Use; Unpaid Work; Gender Inequality; Children's Diets; Technology